TANGGUNG JAWAB PENGANGKUT TERHADAP PENUMPANG AKIBAT TENGGELAMNYA KAPAL KMP BILI TAHUN 2021 - Ghani Al Farozi Sitompul; Elfrida Ratnawati (Fakultas Hukum Universitas Trisakti, 2022)
18 persons received minor injuries as a result of the KMP Bili ship's sinking in West Kalimantan, while 83 cars went down. According to Government Regulation Number 20 of 2010 concerning Water Transportation, what is PT ASDP Indonesia Ferry's obligation for the sinking of the KMP Bili Ship in West Kalimantan in 2021, and how should PT ASDP Indonesia Ferry be made whole for the KMP Bili Ship's passengers? This kind of study employs a normative legal research approach that is analytically descriptive in nature and based on primary and secondary data. Data is gathered via literary data, which is then evaluated using qualitative techniques to reach deductive conclusions. The findings of the study demonstrate that (1) PT ASDP Indonesia Ferry is accountable for the passengers required by Government Regulation Number 10 of 2010 regarding water transportation, Article 180-181, Paragraphs 1-2. (2) Due to a contradiction with the transportation agreement, which specifies the type of obligation the carrier must bear, PT ASDP Indonesia Ferry does not compensate passengers or PT Jasa Raharja Putera.